ショウワ キチ シュウヘン ノ ユウキ エンソ カゴウブツ オセン - 日高, 秀夫; ヒダカ, ヒデオ; 立川, 涼; タツカワ, リョウ; Hidaka, Hideo; Tatsukawa, Ryo (1983)
P(論文) 第22次南極地域観測(1980-1982)において採取した大気, 雪, 海水, 魚介類などの有機塩素化合物(DDT, PCB, HCH)を分析し, 昭和基地周辺の環境濃度と, 基地活動による汚染について検討した。昭和基地の風上方向約13kmのとっつき岬で採取した雪の有機塩素化合物濃度と組成は, みずほ基地の風上約0.6kmの雪とほぼ同じであった。とっつき岬と昭和基地近辺の海水では, 濃度は同レベルであったが, PCB組成が若干異なった。海氷下の水の動きも考慮し, とっつき岬には大気・海水経由での基地からの汚染はないと判定した。基地近辺で採取した底生魚のショウワギス中のPCB濃度は, とっつき岬で採取したショウワギスより約30倍高く(p<0.001), DDTは約2倍高かった(p<0.01)。基地近辺の底生生物は, 南極地域外の魚と比べると低濃度ではあるが, 基地から漏れたPCBによる汚染をかなり受けており, DDTにも若干の影響を受けていると結論づけられる。今後, 基地からの汚染をなくすための, より厳密な廃棄物対策が必要であり, とくに, これらの有機塩素化合物汚染の推移と新たな汚染物質に対応するため, 底生魚を中心とする計画的な試料の採取と保存が望まれる。 DDT, PCB and HCH levels in air, snow, sea water, fish, benthic invertebrate, etc. collected by the 22nd Japanese Antarctic Research Expedition (1980-1982) around Syowa Station were determined and the possibility of leakage of these compounds from the station was discussed. Chlorinated hydrocarbon concentrations and compositions in snow were similar in both the samples at Tottuki Point (about 13km northeast from Syowa Station) and those on the windward (about 0.6km north) of Mizuho Station. The concentrations of these chemicals in sea water samples taken at Tottuki Point and near Syowa Station were in the same level though the compositions of PCB isomers and congeners were somewhat different. Taking water current under ice into consideration, it is assumed that Tottuki Point is still unpolluted from Syowa Station. However, PCB and DDT concentrations of benthic fish, Trematomus bernacchii, collected from near Syowa Station were about thirty times (p<0.001) and twice (p<0.01) higher, respectively, than those at Tottuki Point. So it is concluded that the benthic organisms near Syowa Station are polluted considerably by PCB and slightly by DDT from the station activities, although the PCB and DDT levels in these fish are low compared with those in other oceans. In order to prevent the pollution from station activity, the more strict wastes disposal procedure will be necessary. Systematic sample collection and storage of samples in antarctic environment, in ...